Answer:
The correct option is;
If one reflects a figure across the y-axis, the points of the image can be found using the pattern (x, y) Right-arrow (x, -y).
If one reflects a figure across the y-axis, the points of the image can be found using the pattern (x, y) Right-Arrow (-x, y).
Taking the result from the first reflection (x, -y) and applying the second mapping rule will result in (-x, -y), not (y, x), which reflection across the line y = x should give
Explanation:
We have that for reflection across the x-axis, (x, y) → (x, -y)
For reflection across the y-axis, (x, y) → (-x, y)
Therefore, given that the pre-image before the reflection across the y-axis is (x, -y), we have;
For reflection across the y-axis, (x, -y) → (-x, -y)
For reflection across the line, y = x, gives (x, y) → (y, x) which is not the same as (-x, -y)